Enzyme activity and biochemical changes during production of Lentinula edodes (Berk.) Pegler - Sousa, Maiara Andrade De Carvalho (2018)
AbstractShiitake is an important edible and medicinal mushroom cultivated worldwide. Its cultivation involves a complex process of browning that precedes the primordia initiation. The present work through the evaluation of enzymes, lectin and β-glucan during the cultivation cycle of Lentinula edodes, the degradation of cellulose, hemicellulose and lignin, attempted to correlate these with mushroom yield. Strains UFLA-LE1, UFLA-LE2 and UFLA-LE6 consumed significantly more hemicelluloses than the other three strains with strain LE5 consuming significantly the most lignin of all six strains. Strains UFLA-LE4 and UFLA-LE6 were significantly the most productive. The laccase activity increased continuously until the end of the cultivation for all strains. Manganese peroxidase activities, except for UFLA-LE3, remained relatively stable. On the other hand, lignin peroxidase was the main lignin-modifying enzyme with much higher activity compared to laccase and manganese peroxidase. Tyrosinase activity was stable at an elevated level during the cultivation cycle, dramatically reaching the highest activity at the end of the cultivation period. The amounts of lectin and β-glucan varied greatly depending on the strain and the time of cultivation. Despite the many differences between strains in all evaluated parameters no direct association to the browning process was observed.